Two Years Review of Intraocular Lens Power Calculation in Ophthalmology Department of Saidu Teaching Hospital, Swat - Faiz ur Rahman, Haroon Rashid, Abid Naseem (Pakistan Journal of Ophthalmology, 2007)
Purpose: To determine the mean power of intraocular lens (IOL), keratometeric readings and axial length of the eyeball in patients admitted for cataract surgery with IOL implantation. Materials and Methods: A retrospective review of the intraocular lens power calculation record of patients admitted for cataract surgery with IOL implantation in Ophthalmology Department of Saidu Teaching Hospital, Saidu Sharif, Swat over a period of two years from 1st January 2004 to 31st December 2005 was undertaken. Results: Out of 1359 cases of cataract surgery with IOL implantation admitted during the study period, 649 (47.75%) were male whereas 710 (52.25%) were female. The mean age was 58.71 years. Right eye was operated in 697 (51.3%) cases, while 662 (48.7%) cases were operated on left eye. Mean keratometeric (K1 and K2) readings were 42.65 D and 42.48 D respectively and ranged from 36 D to 52 D in each. Mean axial length of eyeball was 22.52 mm with range from 18 mm to 29.31 mm. Mean power of IOL with 118.0 A constant was 23.17 D with range from 6.50 D to 36.00D. Conclusions: Majority (62.2%) of patients reported in 6th–7th decade of life (51–70 years of age) and they avoid surgery in extreme summer, winter and Ramadan. Mean K1 & K2 readings were 42.65 D & 42.48 D respectively. Mode (most common) K1 & K2 readings were 43 D & 42 D respectively. Mean & mode axial lengths of eyeball were 22.52 mm & 22 mm respectively. Mean & mode powers of IOL with 118.0 A constant were 23.17 D & 23.50 D respectively.